Home to the prairie - Tedrow, Thomas L. (Nashville, Tenn. : T. Nelson Publishers, 1992)
While life goes on in Mansfield, Missouri, Laura agrees to help her elderly father fulfill his dream of returning to their former home on the Kansas prairie.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Frontier and pioneer life -- Missouri -- Fiction; Fathers and daughters -- Fiction